Analisis Pengaruh Motivasi dan Lama Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja sebagai Variabel Intervening pada Puskesmas Batipuh - Redho Syahwaldi Putra; Dori Mittra Candana; Bayu Pratama Azka (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine and attempt to analyze the analysis of the influence of motivation and length of work on employee performance with job satisfaction as an intervening variable at the Batipuh Community Health Center. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample for this study were Batipuh Community Health Center employees. The research results found that there is a positive and significant influence between motivation and job satisfaction. There is a positive and significant influence between Length of Work on Job Satisfaction. There is a positive and significant influence between Motivation on Employee Performance. There is no positive and significant influence between Length of Work on Employee Performance. There is no positive and significant influence between Job Satisfaction and Employee Performance. Job Satisfaction does not mediate Motivation on Employee Performance. Job Satisfaction does not mediate Length of Work on Employee Performance.